2017
DOI: 10.1016/j.bpj.2017.04.046
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of Cholesterol on the Oxygen Permeability of Membranes: Insight from Atomistic Simulations

Abstract: Cholesterol is widely known to alter the physical properties and permeability of membranes. Several prior works have implicated cell membrane cholesterol as a barrier to tissue oxygenation, yet a good deal remains to be explained with regard to the mechanism and magnitude of the effect. We use molecular dynamics simulations to provide atomic-resolution insight into the influence of cholesterol on oxygen diffusion across and within the membrane. Our simulations show strong overall agreement with published exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
90
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(98 citation statements)
references
References 79 publications
8
90
0
Order By: Relevance
“…The rafts are believed to function together with integral and peripheral proteins and could play a role in signal transduction, intracellular transport, and protein sorting in these membranes [1,2]. Both experimental [3] and computational [4] work have demonstrated that addition of cholesterol reduces the permeability of POPC phospholipid bilayers, and experimental work [5] confirms this trend for DOPC. Another characteristic of rafts is the richness in saturated lipids.…”
Section: Introductionsupporting
confidence: 62%
“…The rafts are believed to function together with integral and peripheral proteins and could play a role in signal transduction, intracellular transport, and protein sorting in these membranes [1,2]. Both experimental [3] and computational [4] work have demonstrated that addition of cholesterol reduces the permeability of POPC phospholipid bilayers, and experimental work [5] confirms this trend for DOPC. Another characteristic of rafts is the richness in saturated lipids.…”
Section: Introductionsupporting
confidence: 62%
“…This loosens the molecular alignment, and, consequently, the spacer methylene groups connected to the highly hydrated ammonium groups exhibit enhanced micropolarity near the aggregate surface. A larger partition coefficient of oxygen to these molecular voids is expected, with a diffusion path possibly dominated by water …”
Section: Resultsmentioning
confidence: 99%
“…Indeed, studies on oxygen transport across model and plasma membranes showed that membranes are in general not barriers to oxygen transport into the cell . Meanwhile, oxygen concentration is known to be low in some tissues, notably fiber cells of the eye lens, in which the lens nuclei are protected from oxidative damage and cataracts . The plasma membranes of these fiber cells show extremely high cholesterol content, which is considered to ensure the rigidity of the membrane that contributes to reducing its oxygen permeability .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, OXPHOS damage does not seem to irreversibly prevent, but may rather attenuate HIF-1α stabilization, suggesting that the increased intracellular oxygen concentrations, caused by the lower oxygen consumption, may rapidly equilibrate with the extracellular tensions. Such equilibration probably depends on the cellular membrane permeability to molecular oxygen, which among other is influenced by cholesterol levels and, therefore, lipid metabolism, which is conditioned by the OXPHOS status ( 44 ).…”
Section: Non-canonical Oxygen-dependent Regulation Of Phds By Redistrmentioning
confidence: 99%